Cameroon : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2015)
This Selected Issues paper examines recent performance and reform agenda for Cameroon's state-owned enterprises (SOEs). Cameroon's SOEs are important providers of formal employment and have a large weight in the economy. The profitability and financial autonomy of SOEs have deteriorated in recent years, draining scarce budget resources. In addition, SOEs have amassed significant contingent liabilities in the form of debt and arrears. Weak corporate governance is a key factor in SOEs' poor performance. The reform agenda should include enhancing the monitoring of SOEs, improving disclosure of their contingent liabilities, and strengthening their governance.